Personal Memory, Family Memory, Collective Memory? The Parting Gifts in Egils saga, chapter 61 - Barreiro, Santiago Francisco (Scandinavian-Canadian Studies)
The aim of this article is to discuss the uses of memory focusing on a scene in Egils saga Skalla-Grímssonar, a long prose text written in Iceland in the first half of the thirteenth century. Both the theoretical background and current trends of memory and gift studies as applied to saga scholarship are examined and then used to analyze the role of a detailed exchange of goods between two of the central characters in the saga, Egill and Arinbjǫrn. The final part of the article focuses on studying the scene in its historical context of production, arguing that the saga uses gift exchange to memorialize the lineage of prominent Icelanders likely related to the writing of the saga. Fil: Barreiro, Santiago Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina